2016
DOI: 10.1002/tox.22284
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin gallate sensitizes cisplatin-resistant oral cancer CAR cell apoptosis and autophagy through stimulating AKT/STAT3 pathway and suppressing multidrug resistance 1 signaling

Abstract: Epigallocatechin gallate (EGCG) is a green tea polyphenol that presents anticancer activities in multiple cancer cells, but no available report was addressed for the underling molecular mechanism of cytotoxic impacts on drug-resistant oral squamous cell carcinoma cells. In the present study, the inhibitory effects of EGCG were experienced on cisplatin-resistant oral cancer CAR cells. EGCG inhibited cell viability in a time- and concentration-dependent manner by a sulforhodamine B (SRB) assay. EGCG induced CAR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 42 publications
2
61
0
1
Order By: Relevance
“…At the same time, EGCG promoted the growth inhibition effect of antitumor drugs through autophagy regulation via activation of pro-apoptosis or pro-survival autophagy in cancer cells [3,29,30]. Based on the synergistic effect of EGCG and DOX on osteosarcoma growth inhibition, in second part of this study, it was confirmed that EGCG inhibited DOX induced pro-survival autophagy which would be one of the important molecular mechanism of synergistic effect of EGCG and DOX on osteosarcoma.…”
Section: Disscussionsupporting
confidence: 57%
“…At the same time, EGCG promoted the growth inhibition effect of antitumor drugs through autophagy regulation via activation of pro-apoptosis or pro-survival autophagy in cancer cells [3,29,30]. Based on the synergistic effect of EGCG and DOX on osteosarcoma growth inhibition, in second part of this study, it was confirmed that EGCG inhibited DOX induced pro-survival autophagy which would be one of the important molecular mechanism of synergistic effect of EGCG and DOX on osteosarcoma.…”
Section: Disscussionsupporting
confidence: 57%
“…CAR cells are characterized by its stable resistance to cisplatin as previously described [1, 18, 85, 86]. The cells were cultured in Dulbecco’s modified Eagle’s medium (DMEM) fortified with 10% fetal bovine serum (FBS), 100 U/ml penicillin, 100 μg/ml streptomycin, and 2 mM L-glutamine (Thermo Fisher Scientific) and were incubated at 37 °C with a humidified 5% CO2 air.…”
Section: Methodsmentioning
confidence: 99%
“…The cells were cultured in Dulbecco’s modified Eagle’s medium (DMEM) fortified with 10% fetal bovine serum (FBS), 100 U/ml penicillin, 100 μg/ml streptomycin, and 2 mM L-glutamine (Thermo Fisher Scientific) and were incubated at 37 °C with a humidified 5% CO2 air. The cisplatin-resistant CAR cells were constantly cultured in medium containing 80 μM cisplatin unless otherwise indicated [1, 18, 85, 86]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations